Can't get enough of those Roots of Unity

Algebra Level 3

If w = e 2 π i / 5 w=e^{2\pi{i}/5} , find k = 1 4 1 1 + w k + w 2 k \sum_{k=1}^{4}\frac{1}{1+w^k+w^{2k}}


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

k = 1 4 1 1 + ω k + ω 2 k = 1 1 + ω + ω 2 + 1 1 + ω 2 + ω 4 + 1 1 + ω 3 + ω 6 + 1 1 + ω 4 + ω 8 [ ω 5 = 1 ] = 1 1 + ω + ω 2 + 1 1 + ω 2 + ω 4 + 1 1 + ω 3 + ω + 1 1 + ω 4 + ω 3 = 1 ω 3 + ω 4 1 ω + ω 3 1 ω 2 + ω 4 1 ω + ω 2 [ 1 + ω + ω 2 + ω 3 + ω 4 = 0 ] = 1 ω 3 ( 1 + ω ) 1 ω ( 1 + ω 2 ) 1 ω 2 ( 1 + ω 2 ) 1 ω ( 1 + ω ) = ω 2 + ω 4 1 + ω ω 4 + ω 3 1 + ω 2 = 1 + ω + ω 3 1 + ω + 1 + ω + ω 2 1 + ω 2 = 1 + ω 3 1 + ω + 1 + ω 1 + ω 2 = 2 + ω 3 ( 1 + ω 2 ) + ω ( 1 + ω ) ( 1 + ω ) ( 1 + ω 2 ) = 2 + ω 3 + ω 5 + ω + ω 2 1 + ω + ω 2 + ω 3 = 3 \displaystyle \sum_{k=1}^4 \frac{1}{1+\omega^k + \omega^{2k}} \\ \displaystyle = \frac{1}{1+\omega + \omega^2} + \frac{1}{1+\omega^2 + \omega^4} + \frac{1}{1+\omega^3 + \color{#3D99F6}{\omega^6}} + \frac{1}{1+\omega^4 + \color{#3D99F6}{\omega^8}} \quad \quad \small \color{#3D99F6} {[\omega^5 = 1]}\\ \displaystyle = \frac{1}{\color{#D61F06}{1+\omega + \omega^2}} + \frac{1}{\color{#D61F06}{1+\omega^2 + \omega^4}} + \frac{1}{\color{#D61F06}{1+\omega^3 + }\color{#3D99F6}{\omega}} + \frac{1}{\color{#D61F06}{1+\omega^4 +} \color{#3D99F6}{\omega^3}} \\ \displaystyle = \color{#D61F06}{-}\frac{1}{\color{#D61F06}{\omega^3 + \omega^4}} \color{#D61F06}{-} \frac{1}{\color{#D61F06}{\omega + \omega^3} } \color{#D61F06}{-} \frac{1}{\color{#D61F06}{\omega^2 + \omega^4}} \color{#D61F06}{-} \frac{1}{\color{#D61F06}{\omega + \omega^2}} \quad \quad \small \color{#D61F06}{ [1+\omega + \omega^2 +\omega^3 + \omega^4 = 0]} \\ \displaystyle = -\frac{1}{\omega^3(1 + \omega)} - \frac{1}{\omega(1 + \omega^2)} - \frac{1}{\omega^2(1 + \omega^2)} - \frac{1}{\omega(1 + \omega)} \\ \displaystyle = -\frac{\omega^2+\omega^4}{1 + \omega} - \frac{\omega^4+\omega^3}{1 + \omega^2} \\ \displaystyle = \frac{1+\omega+\omega^3}{1 + \omega} + \frac{1+\omega+\omega^2}{1 + \omega^2} \\ \displaystyle = 1 + \frac{\omega^3}{1 + \omega} + 1 + \frac{\omega}{1 + \omega^2} \\ \displaystyle = 2 + \frac{\omega^3(1 + \omega^2)+\omega(1 + \omega)}{(1 + \omega)(1 + \omega^2)} \\ \displaystyle = 2 + \frac{\omega^3 + \omega^5+\omega + \omega^2}{1 + \omega + \omega^2 + \omega^3} \\ = \boxed{3}

Thanks! You can summarize your work compactly as k = 1 4 1 w k 1 w 3 k = k = 1 4 1 w 6 k 1 w 3 k = k = 1 4 ( 1 + w 3 k ) = 4 + k = 1 4 w 3 k = 3 \sum_{k=1}^{4}\frac{1-w^k}{1-w^{3k}}=\sum_{k=1}^{4}\frac{1-w^{6k}}{1-w^{3k}}=\sum_{k=1}^{4}(1+w^{3k})=4+\sum_{k=1}^{4}{w^{3k}}=\boxed{3}

Otto Bretscher - 5 years, 9 months ago

Log in to reply

Thanks. I was trying to get an easier form. Still don't get the hang of it yet.

Now I got it; the first summation should be k = 1 4 1 ω k 1 ω 3 k \displaystyle \sum_{k=1}^4 \frac{1-\omega^{\color{#D61F06}{k}}}{1-\omega^{3k}}

Chew-Seong Cheong - 5 years, 9 months ago

is there any generalization?

is it like this? If w = e 2. p i . i \n w = e^{2.pi.i\n} then value of summation like that will be n - 2

Dev Sharma - 5 years, 5 months ago

I did same. Nice problem.

Dev Sharma - 5 years, 5 months ago
Vishnu C
May 19, 2015

This was really fun to solve. @Otto Bretscher , I don't know if you saw what I mentioned in my note yesterday, but your problem, one more of those , was a question in yesterday's paper and I solved it pretty quickly. Thank you!

The solution to this problem is based on the repeated application of this identity:

1 + ω + ω 2 + ω 3 + ω 4 = 0. 1+\omega+\omega^2+\omega^3+\omega^4=0.

So

1 + ω + ω 2 = ω 3 ω 4 1 + ω 2 + ω 4 = ω ω 3 1 + ω 3 + ω 6 = 1 + ω 3 + ω = ω 2 ω 4 1 + ω 4 + ω 8 = 1 + ω 4 + ω 3 = ω ω 2 1+\omega+\omega^2=- \omega^3 - \omega^4\\ 1+\omega^2+\omega^4=-\omega-\omega^3\\ 1+\omega^3+\omega^6=1+\omega^3+\omega=-\omega^2-\omega^4\\ 1+\omega^4+\omega^8=1+\omega^4+\omega^3=-\omega-\omega^2

If you apply these identities, you should get:

1 ω 2 ( 1 ω ( ω + 1 ) + 1 ( ω 2 + 1 ) ) 1 ω ( 1 ω 2 + 1 + 1 ω + 1 ) . \frac { -1 }{ \omega ^{ 2 } } (\frac {1 }{ \omega (\omega+1) } +\frac{1}{(\omega^2+1)}) \\-\frac{1}{\omega}(\frac{1}{\omega^2+1}+\frac{1}{\omega+1}).\\

Taking LCM and simplifying the numerator (again using the identities mentioned above) we get

ω 2 + ω + 2 ω ( ω + 1 ) ( ω 2 + 1 ) 1 ω 2 ( ω 2 ω 3 ω 4 ω ( ω 2 + 1 ) ( ω + 1 ) ) . Note that ( ω 2 + 1 ) ( ω + 1 ) = ω 4 . So the denominator gets simplified to -1 = ω 4 × ω -\frac { \omega ^{ 2 }+\omega +2 }{ \omega (\omega +1)(\omega ^{ 2 }+1) } \\ -\frac { 1 }{ \omega ^{ 2 } } (\frac { \omega ^{ 2 }-\omega ^{ 3 }-\omega ^{ 4 } }{ \omega (\omega ^{ 2 }+1)(\omega +1) } ).\\ \text{ Note that }(\omega ^{ 2 }+1)(\omega +1)=-\omega ^{ 4 }.\\ \text{So the denominator gets simplified to -1 = }-\omega^4\times\omega

Now we get:

2 + ω + ω 2 + 1 ω ω 2 = 3 . 2+\omega+\omega^2+1-\omega-\omega^2=\boxed 3.

Thank you for your clear, careful and detailed solution. I'm glad I could help with your papers ;)

Otto Bretscher - 6 years ago

Log in to reply

Nice question sir reshared!

Department 8 - 5 years, 9 months ago

I did the same but i was thinking what to do if we try to generalize this?

neelesh vij - 5 years, 6 months ago
Harry D
Sep 18, 2020

In general, for k k non-negative integer, when w = e 2 π i 3 k + 2 w=e^{\frac{2\pi i}{3k+2}} , that is, when w w is the "smallest-angle" non-trivial ( 3 k + 2 ) - t h (3k+2)\mbox{-}th root of unity, the result of the sum is 2 k + 1 2k+1 .

In fact the result holds for w w being any non-trivial ( 3 k + 2 ) - t h (3k+2)\mbox{-}th root of unity.

In addition, again for k k non-negative integer, when w = e 2 π i 3 k + 1 w=e^{\frac{2\pi i}{3k+1}} , that is, when w w is the "smallest-angle" non-trivial ( 3 k + 1 ) - t h (3k+1)\mbox{-}th root of unity, the result of the sum is, perhaps somewhat surprisingly, k k

Again the result holds for w w being any non-trivial ( 3 k + 1 ) - t h (3k+1)\mbox{-}th root of unity.

Harry D - 8 months, 4 weeks ago
Carsten Meyer
Feb 18, 2019

Another possibility: Expand by 1 + w 2 k 1+w^{2k} to simplify the denominator:

( 1 + w k + w 2 k ) ( 1 + w 2 k ) = w 2 k + k = 0 4 w k = w 2 k k = 1 4 1 1 + w k + w 2 k = k = 1 4 1 + w 2 k w 2 k = 4 + k = 1 4 w 2 k = 3 + k = 0 4 w 2 k = 3 + 0 \begin{aligned} (1+w^k+w^{2k})(1+w^{2k})&=w^{2k}+\sum_{k=0}^4 w^k=w^{2k}\\\\ \Rightarrow \quad\sum_{k=1}^4\frac{1}{1+w^k+w^{2k}}&=\sum_{k=1}^4\frac{1+w^{2k}}{w^{2k}}=4+\sum_{k=1}^4w^{-2k}=3+\sum_{k=0}^4w^{-2k}=3+0 \end{aligned}

Rem.: In the last step, we use that w 2 1 w^{-2}\neq1 is another root of unity of 5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...